2021
DOI: 10.1002/prp2.709
|View full text |Cite
|
Sign up to set email alerts
|

SuperGAG biopolymers for treatment of excessive bladder permeability

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Greenwood-Van Meerveld et al reported on restored bladder function and reduced bladder permeability by intravesical instillation of recombinant human proteoglycan 4 (lubricin, rhPRG4), a highly hydrophilic glycoprotein with anti-inflammatory properties in PS-induced IC in female SD rats [ 41 ]. The same research group also tested a novel high-molecular-weight GAG biopolymer (“SuperGAG”) that was more effective in restoring bladder function and relieving pain compared to CS [ 42 ]. Another emerging class of therapeutic GAGs involves semi-synthetic GAG-ethers (SAGE) offering both mucosal restoration and potent analgesic and anti-inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
“…Greenwood-Van Meerveld et al reported on restored bladder function and reduced bladder permeability by intravesical instillation of recombinant human proteoglycan 4 (lubricin, rhPRG4), a highly hydrophilic glycoprotein with anti-inflammatory properties in PS-induced IC in female SD rats [ 41 ]. The same research group also tested a novel high-molecular-weight GAG biopolymer (“SuperGAG”) that was more effective in restoring bladder function and relieving pain compared to CS [ 42 ]. Another emerging class of therapeutic GAGs involves semi-synthetic GAG-ethers (SAGE) offering both mucosal restoration and potent analgesic and anti-inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been studies dedicated to enhancing the effect of hyaluronic acid and chondroitin sulfate on bladder impermeability, in which “SuperGAGs” were developed as crosslinked GAG molecules with higher molecular weights. For both chondroitin sulfate and hyaluronic acid, these SuperGAGs have demonstrated greater effectiveness in restoring barrier function, characterized by impermeability, compared to regular GAGs [24 ▪ ,25].…”
Section: Discussionmentioning
confidence: 99%
“…SuperGAGs forms a 3-dimensional structure, adhering tightly to the bladder surface and creating a thicker bound water layer. Studies demonstrated that they are more effective in restoring impermeability compared to normal GAGs [ 46 , 47 ].…”
Section: Therapeutic Correction Of Barrier Dysfunctionmentioning
confidence: 99%